Uji Sifat Fisik pH Dan Viskositas Pada Emulsi Ekstrak Bintangur (Calophyllum soulattri Burm. F.) - Tiara Bella Pratiwi; Siti Nani Nurbaeti; Meri Ropiqa; Inarah Fajriaty; Fajar Nugraha; Hadi Kurniawan (Indonesian Journal of Pharmaceutical Education, 2023)
Bintangur (Calophyllum soulattri Burm. F.) is a type of medicinal plant that has quite a lot of benefits such as antioxidant, anti-inflammatory and antibacterial, so it is important to develop it into a dosage form. Emulsions are preparations containing liquid medicinal ingredients or drug solutions dispersed in a liquid carrier. Emulsion preparations are preparations that are more easily absorbed when administered orally. Evaluation of the physical properties of the emulsion was carried out from organoleptic, pH, and viscosity parameters to produce good physical properties because they affect the resulting therapeutic effect. 150 mL of the preparation was made and evaluated for the physical properties of the organoleptic test, pH test, and viscosity test. The pH of the preparation must correspond to the pH of the oral preparation, namely 5-7, and the resulting viscosity must not be too runny or too thick because it is difficult to redisperse. The organoleptic test results of the bintangur extract emulsion had a characteristic yellow-brown color and the aroma of coconut oil with a bitter-sweet taste. The pH test results of the bintangur extract emulsion entered the range for oral preparations 5-7 with an average of 5.936 and the viscosity of the bintangur extract emulsion was 114.2 cP.